Human Rights in the Era of Surveillance: Balancing Security and Privacy Concerns - Nandy, Debasish (UIN Sunan Gunung Djati Bandung, 2023)
In today's rapidly evolving digital landscape, the delicate equilibrium between security imperatives and the protection of individual privacy is under intense scrutiny. This abstract explores the multifaceted challenges posed by the proliferation of surveillance technologies and their impact on human rights. As governments and corporations harness the power of surveillance for security purposes, concerns over privacy violations, data breaches, and potential abuses of power have come to the forefront. This abstract delves into the evolving legal and ethical frameworks governing surveillance practices, highlighting key debates and global perspectives. It also examines the implications for fundamental human rights such as freedom of expression, privacy, and assembly. By examining case studies, emerging technologies, and international efforts to strike a balance between security and privacy, this abstract seeks to shed light on the complex dynamics of this contemporary issue and proposes potential avenues for reconciling these often conflicting interests. Ultimately, it calls for a thoughtful and inclusive dialogue that can guide the development of responsible surveillance policies that respect individual rights and uphold the principles of a free and democratic society.